(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
A new corrosion-spectophotometric method of iron (III) ion determination was created. and the method of immobilization of the obtained reagent on the fiber was developed. Optimal conditions for immobilization of the reagent on the fiber were selected. The dependence of the degree of immobilization on the wavelength and pH of the environment, as well as the effect of the acidity of the environment, was studied. The structure of the complex formed by the immobilized 2,4,6-tri(2-pyridyl)-1,3,5-triazine reagent with iron (III) ion is shown.